Daya Tarik Kampung Wisata Tahu Cibuntu Babakan sebagai Destinasi Wisata Baru di Kota Bandung - Siti Nur Fadilah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The aim of the researchers to conduct this research is to find out about the history and origins of the Cibuntu Babakan area as a tofu industrial area until now a new destination titled "Cibuntu Babakan Tofu Tourism Village" has been established. It was formed because of an idea or notion from a member of the local POKDARWIS (Tourism Awareness Group) who is also the head of the community association 05 Babakan Village, Babakan Ciparay District. The theory used in this research is participation theory. While the method used in this study is descriptive qualitative method, due to the lack of valid data regarding this tourist destination, the researcher went directly to the field to explore the research object, thus making the research object a data. The results showed that the tourist destination "Cibuntu Babakan Tahu Tourism Village" has an attraction, namely with educational tours and culinary tours that may not be found in other areas, also with the local wisdom of the surrounding community making this "Cibuntu Babakan Tahu Tourism Village" become a tourist destination that must be included (Nurlestari, 2016)in the list of tourist trips.